Cultura política e participação: as comunidades virtuais em debate - Monteiro, Marco Aurélio (Universidade Federal de São Carlos, 2013)
The object of this work is the Orkut as a mean of politic socialization. The goal is to analyze the role of new communication and information technologies, specially the Orkut communities Government and Politic , to identify if there are any contribution for expansion and strengthening of a democratic political culture. Our hypothesis is that the Orkut, faced with the possibility of virtual communities creation and discussion referring to political issues, end out creating a public space which corroborates as an agent of political socialization, contributing to amplify politic discussions and for democratic politic culture consolidation. The criterion for selection of communities related to political issues in the Orkut was realized focusing in the diversity of political issues positioning, such as support, rejection and evaluation about politic and democracy. The methodology for this analyze correspond to DAIA criterion , once this criterion is not limited only in thinking communication in terms of instrumentalization and technique, but as a process of social relationship. In this way, we aimed trough this Orkut study, mainly of its communities, to investigate the role of NTCI s in the consolidation of a democratic politic culture and to contribute for the investigation about digital democracy in democratic process.
Keywords: Ciência política; Novas tecnologias da comunicação; Comunidade virtual; Cultura política; Democracia; Participação; Novas tecnologias de informação e comunicação; Orkut; Mídia; Socialização política; New technologies of information and communication; Orkut; Virtual community; Cultural politic; Democracy; Media; Political socialization; Participation; CIENCIAS HUMANAS::CIENCIA POLITICA